The new Spanish Autonomous Communities fiscal stability framework - M. Jose Prieto; Agustin Manzano (European Regional Science Association (ERSA), 2004)
From to beginning of year 2002, the Spanish Autonomous Communities (CC. AA.) fiscal performance is conditioned by a new legal framework compounded from the financial agreement and the legislation on budget stability. This new framework implies a change in the CC. AA. fiscal behaviour. Are the CC. AA. ready to provide its citizens the public services they demand and fulfil its fiscal stability commitments? Are all the CC. AA. in the same position? Using political economic models and data on past budget execution, this paper is aimed at shedding light over the factors that jeopardize the CC. AA. budget stability in the future and the differences between CC. AA. relevant to its fiscal performance. JEL classification: H61, H62, H71, H72, H77
Keywords: H61; H62; H71; H72; H77; 330